PERBEDAAN DOSIS PUPUK ORGANIK CAIR DAN JENIS KLON RATOON 1 TERHADAP PERTUMBUHAN TANAMAN TEBU (Saccharum officinarum (L)) DI KECAMATAN KEBOMAS - GRESIK - Achmad Hafidh Wahyudi; Setyo Budi; Endah Sri Redjeki (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2022)
Sugarcane (Saccharum officinarum (L)) is the raw material for the white sugar industry. One of the factors for the decline in sugar productivity is the level of land fertility that continues to decline, which is caused by modern agriculture placing more emphasis on the use of inorganic fertilizers. This study aims to determine the effect of organic matter on the growth of sugarcane plants. This research was conducted at the Experimental Garden of the Faculty of Agriculture, UMG in March - June 2022. The experimental design used a split plot with two factors. The first factor was clone (V), namely V1 (clone SB03), V2 (clone SB19) and V3 (clone SB33). The second factor is the dose of guano liquid organic fertilizer consisting of 3 levels, namely P1 (control), P2 (liquid guano fertilizer 15 ml per 15 liters of water) and P3 (liquid guano fertilizer 30 ml per 15 liters of water). Each was repeated four times so that there were 36 treatment combinations. The growth variables measured were plant height, number of leaves, number of tillers and stem diameter. Data analysis using Anova Test F. If there is a significant difference then proceed with DMRT 5%. Furthermore, regression tests (correlation), and heritability tests. The results of the study did not show a significant difference in the interaction. Fertilizer treatment showed no significant difference in all observation variables. The clone type treatment showed significant differences at the age of 18 MSK (weeks after kepras) in plant height and stem diameter variables as well as in leaf variables at 12 and 14 MSK.